Alterations of HDL's to piHDL's Proteome in Patients with Chronic Inflammatory Diseases, and HDL-Targeted Therapies - Veronika Vyletelová; Mária Nováková; Ľudmila Pašková (MDPI AG, 2022)
Chronic inflammatory diseases, such as rheumatoid arthritis, steatohepatitis, periodontitis, chronic kidney disease, and others are associated with an increased risk of atherosclerotic cardiovascular disease, which persists even after accounting for traditional cardiac risk factors. The common factor linking these diseases to accelerated atherosclerosis is chronic systemic low-grade inflammation triggering changes in lipoprotein structure and metabolism. HDL, an independent marker of cardiovascular risk, is a lipoprotein particle with numerous important anti-atherogenic properties. Besides the essential role in reverse cholesterol transport, HDL possesses antioxidative, anti-inflammatory, antiapoptotic, and antithrombotic properties. Inflammation and inflammation-associated pathologies can cause modifications in HDL's proteome and lipidome, transforming HDL from atheroprotective into a pro-atherosclerotic lipoprotein. Therefore, a simple increase in HDL concentration in patients with inflammatory diseases has not led to the desired anti-atherogenic outcome. In this review, the functions of individual protein components of HDL, rendering them either anti-inflammatory or pro-inflammatory are described in detail. Alterations of HDL proteome (such as replacing atheroprotective proteins by pro-inflammatory proteins, or posttranslational modifications) in patients with chronic inflammatory diseases and their impact on cardiovascular health are discussed. Finally, molecular, and clinical aspects of HDL-targeted therapies, including those used in therapeutical practice, drugs in clinical trials, and experimental drugs are comprehensively summarised.